2001
DOI: 10.1177/088506660101600603
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Weaning from Mechanical Ventilation

Abstract: Invasive mechanical ventilation can successfully support the patient with acute respiratory failure, but it is associated with considerable risks. Numerous complications of invasive mechanical ventilation have been identified, and these may contribute to increased mortality. Therefore after clinical improvement has occurred, considerable emphasis is placed on expeditiously freeing the patient from the ventilator. This process of getting a patient off mechanical ventilation has been variably termed weaning, lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 142 publications
1
8
0
8
Order By: Relevance
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 72%
See 1 more Smart Citation
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 72%
“…Early extubation was defined as mechanical ventilation in period shorter than 24 hours (practically shorter than 24 hours, usually 4-8 hours) (1)(2)(3)(4). Determination of the optimal moment for extubation is based on clinically and laboratory factors, that indicates possibility of appropriate blood gas exchange during spontaneously breathing.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the ability to augment cardiac output during an unsuccessful weaning trial may indicate noncardiac causes, such as muscle weakness, malnutrition, increased resistive or elastic loads, endocrinopathies, or anxiety, as the cause of the lack of success. 18,20,21 Previous research 6 indicates that a major proportion of patients who have an unsuccessful SBT have associated cardiac dysfunction. Using an invasive measure of intravascular pressure, Jubran et al 22 compared the continuous recording of mixed venous oxygen saturation in patients whose weaning trial was successful with that of patients whose trial was unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…This is not yet entirely possible, according to many authors and medical associations. 7,8 Over recent years, many different controlled studies of adult patients have been conducted in attempts to identify objective and precise parameters and criteria that can determine the most suitable moment for withdrawing the respirator and performing extubation. Even with experienced medical teams, routine application of the clinical and laboratory criteria indicative of successful weaning still results in significant extubation failure and reintubation rates.…”
Section: Introductionmentioning
confidence: 99%